2004
DOI: 10.1189/jlb.1203656
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two immunogenic domains of the prion protein—PrP—which activate class II-restricted T cells and elicit antibody responses against the native molecule

Abstract: Recent reports suggest that immunity against the prion protein (PrP) retards transmissible spongiform encephalopathies progression in infected mice. A major obstacle to the development of vaccines comes from the fact that PrP is poorly immunogenic, as it is seen as self by the host immune system. Additional questions concern the immune mechanisms involved in protection and the risk of eliciting adverse reactions in the central nervous system of treated patients. Peptide-based vaccines offer an attractive strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 37 publications
2
45
1
Order By: Relevance
“…The three PrP peptides selected in the present study are naturally processed and presented by APC as shown after immunization of Prnp Ϫ/Ϫ mice with a plasmid encoding the entire PrP sequence (18). However, peptide immunization with CFA as adjuvant could not induce a detectable PrP-specific response in PrP ϩ mice.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The three PrP peptides selected in the present study are naturally processed and presented by APC as shown after immunization of Prnp Ϫ/Ϫ mice with a plasmid encoding the entire PrP sequence (18). However, peptide immunization with CFA as adjuvant could not induce a detectable PrP-specific response in PrP ϩ mice.…”
Section: Discussionmentioning
confidence: 90%
“…C57BL/6 wild-type mice were immunized twice at 10-to 15-day intervals with P39-67, P98-127, P143-172, and P158-187 (Table I) together with either CFA or CpG in IFA. These four peptides were selected from 13 overlapping 30-mers because of their ability to stimulate a T cell response in Prnp Ϫ/Ϫ mice (18); all other peptides did not induce a detectable T cell proliferation. P39-67 was used as a negative control in further studies.…”
Section: Generation Of T Cell Responses To Prp Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…PrP 97-128 and PrP 158-187 are two immunogenic peptides recognized by CD4 + T cells in a class II, I-A b context. They were previously identified out of a bank of 13 peptides, mostly 30-mers, with a 15 aa overlap on each side (Gregoire et al, 2004). The bank was synthesized by NeoMPS (Strasbourg, France) with a minimum of 80 % purity.…”
Section: Methodsmentioning
confidence: 99%
“…Immunization of mice made genetically deficient for PrP (Prnp 2/2 ) with PrP 97-128 induces moderate T-cell responses but good Ab secretion, including Abs to native, cell-bound PrPc, whereas PrP 158-187 elicits strong cellular responses but few Abs to the native protein (Gregoire et al, 2004). When injected into wt mice, the same peptides trigger no response unless they are administered together with a potent adjuvant such as CpG-ODN (Rosset et al, 2004 (Fig. 3b).…”
Section: Introductionmentioning
confidence: 99%